PENGARUH PEMBERIAN SUSU KEDELAI KUNING (Glycine max (L.) Merr.) TERHADAP KADAR KOLESTEROL TOTAL PADA PRIA HIPERKOLESTEROLEMIA - Santi Widiasari; Mutiara , Mutiara Muslimah; Eliya Mursyida (Jurnal Kesehatan Islam : Islamic Health Journal, 2023)
Abstract.Hypercholesterolemia is an increase in blood cholesterol levels, which is more than 200 mg / dl. In Indonesia, 9.3% of the incidence of hypercholesterolemia is in productive age, namely the age range of 25-40 years. One of the drugs for hypercholesterolemic sufferers is a statin which is believed to reduce LDL levels and inhibit the formation of cholesterol by indirectly affecting cholesterol levels in the blood. Soybeans are known to reduce cholesterol levels because they contain isoflavones that bind to the endoplasmic reticulum, then increase the Low-density lipoprotein (LDL) receptors in the liver. So that LDL levels in plasma are measured to be low. Objective: To analyze the effect of giving soy milk on cholesterol levels in hypercholesterolemic men. Method: Experimental using the design "One-Group Pretest-Postest Design". The sample consisted of 10 men with hypercholesterolemia given 250 ml / day for 2 weeks. Results: The results showed a significant value of p <0.05. The average total cholesterol level in the provision of soy milk decreased by 6.2 mg / dl. Conclusion: The provision of soy milk has an effect on total cholesterol levels in hypercholesterolemic men. Kata Kunci antibakteri; Hiperkolesterolemia, kolesterol, susu kedelai